EFFECT OF CARALLUMA FIMBRIATA EXTRACT ON APPETITE & LIPID PROFILE IN RATS FED WITH HYPERCALORIE/CAFETERIA DIET - BHARATHA AMBADASU; DANGE S V; WALI R S; WORLIKAR P S (International Journal of Pharma and Bio Sciences, 2013)
To study the Effect of Caralluma Fimbriata extract (CFE) on appetite & lipid profile in rats fed with hypercalorie/cafeteria diet. Methods: Wistar rats weighing 180-240g were randomly divided into three groups (n=6 each); i) Control, ii) Cafeteria Diet (CD), and iii) Cafeteria diet + CFE. CFE was administered at 100 mg/kg/day p.o. for 50 days. Food intake, animal’s bodyweight, blood glucose, serum lipid levels were measured –at baseline, every 10 days and at term. Liver Function Tests & Renal Function Tests were measured at baseline and at term. Results: Treatment with CFE at a dose of 100 mg/kg/day significantly (P <0.05) reduced the increase in body weight and lipid profile levels as compared to the CD control group. Conclusions: Caralluma fimbriata extract prevented gain in body and alterations in lipid profile caused by Cafeteria Diet. Hence, this agent might be useful in treatment of obesity.